1996
DOI: 10.1016/0376-6357(95)00031-3
|View full text |Cite
|
Sign up to set email alerts
|

Selecting dominants and subordinates at conflict outcome can confound the effects of prior dominance or subordination experience

Abstract: Individuals with a previous experience of dominance are likely to be dominants in further encounters. To test this effect, individuals with a previous experience of dominance are used for the experiments. One way to obtain such individuals is to let opponents «self-select»: encounters between pairs of more or less equivalent opponents are staged and one selects ex post facto the dominant and subordinate from the ensuing conflict. This paper formally shows that the selection of dominant and subordinate animals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 6 publications
1
31
0
Order By: Relevance
“…Bégin et al (1996) have demonstrated that in experiments allowing winners and losers to self-select, what appears to be the result of recent experience may actually be caused by uncontrolled differences between individuals on attributes associated with dominance ability. They suggest that by imposing victory or defeat (by retaining only winners and losers that were predicted to win or lose in experimentally rigged contests), such a confounding is most probably reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bégin et al (1996) have demonstrated that in experiments allowing winners and losers to self-select, what appears to be the result of recent experience may actually be caused by uncontrolled differences between individuals on attributes associated with dominance ability. They suggest that by imposing victory or defeat (by retaining only winners and losers that were predicted to win or lose in experimentally rigged contests), such a confounding is most probably reduced.…”
Section: Discussionmentioning
confidence: 99%
“…This happened in only 24.4% (60/246) of all planned cases, indicating that size superiority combined with residency provided a highly significant advantage at this step of the research (p=q=½, x=60, N=246, P<.001 to a binomial test). This approach ensured that social experience and statistical selection were not confounded effects (Bégin et al, 1996).…”
Section: Experimental Designmentioning
confidence: 99%
“…Nonetheless, comb and wattles size was co-selected with the repartition of the birds into victorious and defeated ones at the issue of rigged contests in which victory and defeat had been correctly forecast. This raises serious questions either about the effectiveness of the control procedure suggested by Bégin et al (1996), or about the generality of co/self-selection in the present domain.…”
Section: Discussionmentioning
confidence: 98%
“…Its mutual assessment when there is a conflict between two unfamiliar hens is surely influential upon which bird will first attack the other. Bégin et al (1996) have demonstrated that , in experiments allowing winners and losers to self-select, what appears to be the result of recent experience may actually be caused by uncontrolled differences between individuals on attributes associated with dominance ability. They suggest that by imposing victory or defeat by retaining only winners and losers that were predicted to win or lose in experimentally rigged contests, such a confounding is most probably reduced.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation